Gender differences in occupational mobility: evidence from Portugal - Crespo, Nuno (2014)
In this paper we evaluate if gender influences the pattern of upward and downward occupational mobility. With data for Portugal in the period 1998-2009, we find that women have a lower probability of upward mobility and a higher probability of downward mobility. The results also reveal the importance of some other determinant factors, especially education and initial occupation. Additionally, considering an analysis by quartiles (taking as reference a ranking based on average wages), we confirm that the determinants of occupational mobility depend on the ranking of the initial occupation. This analysis allows us to conclude that the unfavorable pattern of occupational mobility in the case of women is due, essentially, to the disadvantage they have at the bottom of the distribution. On the contrary, in the top occupations, the results suggest the existence of equality between genders.